Towards requirements for the dynamic sourcing of Open Corpus Learning Content - LAWLESS, SEAMUS SEAN TOMAS; DAGGER, DECLAN; WADE, VINCENT PATRICK (My University, 2006)
The dynamic sourcing of Open Corpus Learning Content is a complex and resource intensive process. However, modern technologies and methods can facilitate an efficient content identification and acquisition process. Several bodies of research have begun investigating the application of modern technologies to problems in this area, such as automatic semantic tagging of content, however none have managed to successfully implement a scenario whereby the requirements of elearning environments can be leveraged to accurately source and retrieve learning content. This paper describes the initial requirements for successfully sourcing and harvesting open corpus learning content, the architecture for an Open Corpus Content Sourcing service (OCCS) and a scenario for its use in Personalised eLearning.
eLearn 2006: World Conference on E-Learning in Corporate, Government, Healthcare and Higher Education
PUBLISHED
Keywords: Open Corpus Learning Content; Personalised eLearning